Physical Vs. Virtual Classroom: A Comparative Study Of Teacher Effectiveness Before And During Covid-19 Pandemic - Singh, Bushra S. P. (Gyan Management Journal, 2020)
In the wake of the Covid-19 Pandemic, it became mandatory for  educational insititutions to shift  operations online and resume classes. In order to capture the difference in the quality of teaching  arising due to the use of online platform, this study collected perceptions of teachers on their teaching  effectiveness in the physical setting and the virtual environment. For this purpose, data was collected  from  224  teachers  using  the  Teacher  Effectiveness  Scale  (Jani,  Shahid,  Thomas,  Francis  &  Francis,2018). Descriptive Statistics, Paired Samples T-Test and Independent Samples T-Test were  used for analysis. It was found that quality of teaching was significantly higher in traditional settings.  Also, it was found that the teaching quality of female teachers was more severely affected than male  teachers due to the use of online platforms. No differences in teaching quality between real and online  classrooms were found across age groups and tenure. Suggestions for improvement include online  training sessions for teachers where technical skills and online pedagogical skills may be imparted.  This  study  has  bridged  an  important  gap  by  presenting  a  comparison  of  physical  and  virtual  classrooms from the teacher's perspective.
Keywords: Teacher Effectiveness; Quality of Teaching; Covid-19 Pandemic; Teachers; Lockdown; Online Teaching; Physical Classroom; Virtual Classroom